Minimal change disease in a patient receiving checkpoint inhibition: Another possible manifestation of kidney autoimmunity?. Issue 5 (29th June 2020) - Vaughan, Erin; Connolly, Elizabeth; Hui, Mun; Chadban, Steven
Abstract: Background: Nivolumab has been associated with immune‐related adverse events, including nephritis, with acute interstitial nephritis being the most commonly reported renal manifestation. Case: We describe the first case to our knowledge of minimal change disease with nephrotic syndrome associated with the PD‐1 checkpoint inhibitor, Nivolumab. Minimal change disease has been reported with other immune checkpoint inhibitors; however, this is the first reported case with Nivolumab. We report development of nephrotic syndrome with acute kidney injury in a 57‐year‐old man, 1 month after commencement of Nivolumab for metastatic squamous cell carcinoma of the tongue. Minimal change disease was confirmed by renal biopsy. Management with corticosteroids and cessation of Nivolumab failed to improve kidney function or nephrosis. Conclusion: This case adds to current literature identifying minimal change as an additional complication of immune checkpoint inhibitor‐associated acute kidney injury. Given the increasing use of immune checkpoint inhibitors for a range of malignancies, nephrologists, oncologist and generalists should be aware of the spectrum of kidney pathologies associated with their use.